2021
DOI: 10.1021/acs.jpca.1c00211
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Modeling of Reactions of Addition of H2 Molecules to Magnesium Clusters Mg17M Doped with Atoms M of Transition 3d Elements

Abstract: Density functional theory calculations of potential energy surface (PES) have been performed for elementary hydrogenation reactions Mg 17 M + H 2 → Mg 17 MH 2 of magnesium clusters Mg 17 M doped by transition 3d metals (M = Ti−Ni), and for consecutive reactions Mg 17 Ni + nH 2 → Mg 17 NiH 2n of addition of n hydrogen molecules to Ni-doped clusters Mg 17 Ni and Mg 17 NiH 2 . Energetic, geometric, and spectroscopic features of intermediates and transition states along the minimum energy pathway have been found, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Following the pioneering work of Nonose and co-workers on the chemisorption of small clusters of aluminum with hydrogen, the reaction mechanism of charged and neutral aluminum clusters and their doped species with H 2 has been later explored in terms of both theoretical and experimental approaches. The geometric and electronic structures of hydrogenated scandium, titanium, and zirconium clusters have been examined by Kumar et al and Sheng et al , Swart and co-workers investigated the H 2 adsorption on 3d transition metal clusters in combined infrared spectroscopy and density functional study . Density functional theory (DFT) calculations have been performed to understand the adsorption and dissociation pathway of H 2 molecule on magnesium doped with transition metal atoms. The bonding characters and adsorption energies of H 2 molecules on pure and decorated boron fullerenes/spheres have been extensively studied due to their potential for hydrogen storage media. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the pioneering work of Nonose and co-workers on the chemisorption of small clusters of aluminum with hydrogen, the reaction mechanism of charged and neutral aluminum clusters and their doped species with H 2 has been later explored in terms of both theoretical and experimental approaches. The geometric and electronic structures of hydrogenated scandium, titanium, and zirconium clusters have been examined by Kumar et al and Sheng et al , Swart and co-workers investigated the H 2 adsorption on 3d transition metal clusters in combined infrared spectroscopy and density functional study . Density functional theory (DFT) calculations have been performed to understand the adsorption and dissociation pathway of H 2 molecule on magnesium doped with transition metal atoms. The bonding characters and adsorption energies of H 2 molecules on pure and decorated boron fullerenes/spheres have been extensively studied due to their potential for hydrogen storage media. …”
Section: Introductionmentioning
confidence: 99%
“… 17 Density functional theory (DFT) calculations have been performed to understand the adsorption and dissociation pathway of H 2 molecule on magnesium doped with transition metal atoms. 18 20 The bonding characters and adsorption energies of H 2 molecules on pure and decorated boron fullerenes/spheres have been extensively studied due to their potential for hydrogen storage media. 21 − 29…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al have reported that adding Ti and Nb into M g 55 cluster enhances the stability and also improve the hydrogenation kinetics [38].Very recently, Samantaray et al have been able to synthesize NiMg alloy nanocomposites with up to 5.4 wt% hydrogenation capacity [40]. The issue of hydrogenation kinetics in M g 17 M clusters doped with different 3d transition metal atoms (M) have recently appeared in a series of DFT studies by Charkin and Maltsev [41,42,43,44]. They have confirmed Mg17Ni cluster to have the most favourable reaction kinetics in forming M g 17 M H 2 systems [41].…”
Section: Introductionmentioning
confidence: 99%
“…In another study Cui et al have explored the hydrogen storage properties of a series of Mg-TM (TM=Ti, Nb, V, Co, Mo, Ni) nanocomposites and ranked the dehydro-genation performance as [42]. Charkin and Maltsev have recently studied the reaction kinetics for the hydrogenation of different 3d transition metal (M) doped M g 17 M clusters [43,44,45]. They have reported that Ni shows the most favourable reaction kinetics in the formation of M g 17 M H 2 systems [45].…”
Section: Introductionmentioning
confidence: 99%
“…Charkin and Maltsev have recently studied the reaction kinetics for the hydrogenation of different 3d transition metal (M) doped M g 17 M clusters [43,44,45]. They have reported that Ni shows the most favourable reaction kinetics in the formation of M g 17 M H 2 systems [45]. Trivedi and Bandopadhyay studied the hydrogen adsorption on Rh and Co doped Mg clusters in two different DFT studies and reported M g 5 Co and M g 9 Rh as the most effective hydrogen storage clusters [29,31].…”
Section: Introductionmentioning
confidence: 99%